(untitled) (Itinera, 2018)
By contrasting Walter Benjamin’s fragmentary theory of quotation to the different ways his work has itself undergone quotation thus far, a new insight can be gained into the perception of the materiality and visuality of texts. The so-called Passagen-Werk, the project on the Parisian Arcades which Benjamin pursued for more than ten years until the end of his life, is the overflowing, yet voided space where this crossing takes place.